Do we get it right? Radiation oncology outpatients' perceptions of the patient centredness of life expectancy disclosure. Issue 12 (26th June 2013) - Mackenzie, Lisa J.; Carey, Mariko L.; Paul, Chris L.; Sanson‐Fisher, Rob W.; D'Este, Catherine A.
Abstract Objective A patient‐centred approach to discussing life expectancy with cancer patients is recommended in Western countries. However, this approach to eliciting and meeting patient preferences can be challenging for clinicians. The aims of this study were the following: (i) to examine cancer patients' preferences for life expectancy disclosure; and (ii) to explore agreement between cancer patients' preferences for, and perceived experiences of, life expectancy disclosure. Methods Cancer patients undergoing radiotherapy treatment in metropolitan Australia completed a cross‐sectional touchscreen computer survey including optional questions about their life expectancy disclosure preferences and experiences. Results Of the 208 respondents, 178 (86%) indicated that they would prefer their clinician to ask them before discussing life expectancy, and 30 (14%) indicated that they would prefer others (i.e. clinicians, family) to decide whether they were given life expectancy information. Of the 175 respondents who were classified as having a self‐ determined or other‐determined disclosure experience, 105 (60%) reported an experience of life expectancy disclosure that was in accordance with their preferences. Cohen's κ was −0.04 (95% CI, −0.17, 0.08), indicating very poor agreement between patients' preferences for and perceived experiences of life expectancy disclosure (p = 0.74). Conclusions In light of patient‐centred prognosis disclosure guidelines, our findings of a majority preference for, and experience of, a self‐determined approach to life expectancy disclosure amongst radiation oncology patients are encouraging. However, poor agreement between preferences and experiences highlights that additional effort from clinicians is required in order to achieve a truly patient‐centred approach to life expectancy disclosure. Copyright © 2013 John Wiley & Sons, Ltd.